Adherence and Associated Factors towards Antidiabetic Medication among Type II Diabetic Patients on Follow-Up at University of Gondar Hospital, Northwest Ethiopia. (17th January 2016) - Abebaw, Mastewal; Messele, Anteneh; Hailu, Mignote; Zewdu, Fisseha
Abstract : Background . The prevalence of diabetes mellitus (DM) is rising worldwide and is more in the developing countries which unfortunately are already suffering from communicable diseases. The aim of this study was to assess adherence and associated factors towards antidiabetic medication among type II diabetic patients in University of Gondar Hospital, Diabetic Clinic, Gondar, Northwest Ethiopia. Methods . Institutional based cross-sectional study was conducted. Systematic sampling technique was used. Morisky Medication Adherence Scale (MMAS) scores were used for labeling patients as adherent or nonadherent. Data were entered and analyzed using SPSS version 20. To see the association of variables logistic regression with OR and 95% CI was done. Results . A total of 288 study participants were interviewed with response rate of 100%. The level of adherence was found to be 85.1%. Factors found to be significantly associated with antidiabetic medication adherence were level of education (AOR = 14.27, 95% CI = 3.0, 67.82), duration of diabetes (AOR = 6.10, 95% CI = 2.03, 18.34), and knowledge about DM and its medications (AOR = 28.05, 95% CI = 8.96, 87.8). Conclusions and Recommendations . Large proportion of respondents in this study were found to be adherent to their antidiabetic medications. Level of education, duration of diabetes, and knowledge about DM and its medication were significantly associated with antidiabetic medication adherence of patients. Health education including adherence counseling to create awareness towards DM and its medications is mandatory.